All‐in‐One Theranostic Platform Based on Hollow Microcapsules for Intragastric‐Targeting Antiulcer Drug Delivery, CT Imaging, and Synergistically Healing Gastric Ulcer (Small 9/2022). Issue 9 (3rd March 2022) - Wang, Qi; Xu, Yu; Xue, Rui; Fan, Jingmin; Yu, Hang; Guan, Jiawei; Wang, Hongzheng; Li, Min; Yu, Wei; Xie, Zhiyong; Qi, Rong; Jia, Xin; et al.
Abstract : All‐in‐One Theranostics In article number 2104660, Xin Jia, Bo Han, and co‐workers coordinate bismuth ions and natural polyphenols into a metal phenolic network (MPN). Tetracycline is used as a model drug to evaluate the efficacy and drug carrying capacity of the MPN. The results show that the drug delivery system constructed in this work provides a versatile intragastric‐targeting all‐in‐one theranostic drug delivery platform for gastric ulcer therapeutics.